Pilihan Metode Manajemen Proyek dan Pengembangan Aplikasi pada Perusahaan Pemula Pengembang Perangkat Lunak di Jakarta - Hudiarto, Hudiarto (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The ability of Indonesian computer practitioners in making business applications programs which are both internet-based and non-internet-based is already satisfactory. Their work can be viewed from a variety of business applications commissioned by many local, national and international levels. The problem often encountered is the lack of project management at the company maker of project business applications. It may affect the availability of adequate documentation as part of the project output. In this paper the author recommends software developing using a concept by McConnell (1996) that depends on the project’s characteristics and scope. McConnell is one of the mainstays of Microsoft experts who experiences many years as a project leader software made by the company. The object of this paper is to study several beginner companies of software developer in Jakarta. The software coverage is especially for profit company and both internet-based and non internet-based applications. From a comparison of several projects it is found that that late delivery often occur since the methid is implemented less stringent. This study is expected to be useful for other novice developers who get difficulty in submission software on time, right cost and right quality at the scope of the software that has been agreed.